TEACHING READING BY USING COMIC STRIPS TO IMPROVE JUNIOR HIGH SCHOOL STUDENTS’ COMPREHENSION - Yondrizal Maulana; Fitrawati Fitrawati (Journal of English Language Teaching, 2017)
Reading comprehension is the ability to get information in a text and be able to interpret it appropriately. Reading comprehension is combination information from a text and own background knowledge to understanding the message conveyed by the author. However, not all of the Junior High School students learn reading comprehension easily which is caused by the learning activity which is not really interesting so that the students get bored.A blend of methods and media which the writer trying to describe in this paper, is expected to improve students' skills in reading comprehension. The media used is comic strips and theapplying method is PQRST. It is kinds of activity where students are ask to read a comic and trying to understand quickly what the story is contained in the comic.